Determinan Kepuasan Nasabah Dalam Menggunakan Mobile-Banking Pada Bank Syariah Indonesia Di Kota Banda Aceh - Ilyas, TM. Syahrizal; Wardah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
The purpose of this study is to measure and analyze the impact of trust, religiosity, efficiency, and service quality on the satisfaction in using mobile-banking among the customers of Bank Syariah Indonesia (BSI)in Banda Aceh City, Indonesia. Togather the data, the study distributed questionnaires to a 100 selected the BSI customers in the city using a purposive sampling technique. Used a linear regression analysis, the study found that trust, efficiency, and service quality have a significant positive impact on the customer satisfaction in using BSI' mobile-banking BSI. Meanwhile, the religiosity has in significant effect on the customer satisfaction in using mobile-banking of the BSI These findings show the importance of enhancing trust, efficiency, and service quality to promote satisfaction of the BSI's customers in using mobile-banking.